The relationship between the kick start and lower-limbs muscle strength in swimming - Suito, H.; Nunome, H.; Ikegami, Y. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Recently, the competing swimming was introduced the new start block with starting block. The start is one of the most important factors for swimming performance. The kick start using the new start block was reported significant improves start time than the traditional start (Ozeki et al., 2011). The kick start is like track start but uses a starting block by backward leg. The purpose of this study was to investigate the relationship between the start time and maximal isometric strengths of forward and backward legs. Methods: Subjects in this study were 5 males Japanese competitive swimmers (Age = 20.4 ± 0.5 years, Height = 175.6 ± 7.0 cm, Weight = 65.7 ± 6.1 kg, freestyle(n=3), breaststroke(n=1), butterfly(n=1)). The start time of the subjects was measured by digital camera operating at 30 Hz in the transit time of head of 5 m from takeoff of foot during race of the national intercollege competition swimming. Maximal isometric strengths of knee extension were determined as peak torques using an isokinetic dynamometer. Results: The average time of start at 5 m was 0.75 ± 0.04 s. The average maximal isometric strength of forward leg was 196.0 ± 42.1 Nm. The average maximal isometric strength of backward leg was 202.6 ± 67.4 Nm. Moreover, a significant correlation was obtained between the start time to 5 m and maximal isometric strength of forward leg (r=-0.911, P<0.05). However, there was no significant correlation between the maximal isometric strength of backward leg and the start time to 5 m. Discussion: From these results, it is suggested that isometric maximal strength of the forward knee extension influence the kick start. On the other hand, isometric maximal strength of the backward knee extension has an insignificant effect on the kick start. Therefore, it is possible that develop muscle strength of the forward knee extensiton was effective to improve of the kick start performance in competitive swimming.